Focused Cardiac Assessment in Kidney Care - Vineet Veitla; Bhavna Bhasin (POCUS Journal, 2022)
Point of care ultrasonography (POCUS) is considered to be a very useful and informative extension of the bedside physical exam. The information obtained from POCUS allows for real time assessment for expedited decision making to improve efficiency in patient care and management. Many programs across the country are now incorporating POCUS into their training schedules to allow their residents, fellows, and faculty to gain competence in the techniques and varied clinical uses of POCUS [1-3]. In nephrology, POCUS has been used at the bedside for access planning, dialysis catheter placement, and to guide kidney biopsies to mention a few applications [4]. There is a wide scope for POCUS in nephrology in addition to kidney and bladder assessment. This includes focused cardiac ultrasound to evaluate the heart for structural and functional abnormalities and lung ultrasound as well. These bedside ultrasound assessments help with point of care management decisions pertaining to volume assessment in acute and chronic kidney disease, adjustment of ultrafiltration goals in dialysis patients, and evaluation of hypotension and dyspnea.